The metabolism-immune axis in colorectal cancer: remodeling the tumor microenvironment through metabolite signaling - Hu, Shaofan; Heng, Hui; Yang, Fang; Wang, Meng; Liu, Guoxiang; Xiang, Yuancai; Miao, Hongming (Frontiers in Immunology, 2025)
Metabolic reprogramming is a defining hallmark of tumors, and plays a pivotal role in sustaining malignant growth by rewiring core bioenergetic and biosynthetic pathways. Beyond supporting tumor cell proliferation, survival, and metastasis, it profoundly shapes the tumor microenvironment through nutrient competition, accumulation of immunosuppressive metabolites, and modulation of immune cell function, thereby facilitating immune evasion and therapy resistance. This review comprehensively elaborates on metabolic reprogramming in colorectal cancer, covering key alterations in glucose metabolism (Warburg effect), tricarboxylic acid cycle remodeling, lipid biosynthesis/oxidation, cholesterol metabolism, and amino acid (glutamine, methionine, tryptophan, arginine) metabolism. It further dissects how these metabolic shifts impact the tumor microenvironment in colorectal cancer, including their effects on effector immune cells (CD8+ T cells, NK cells), immunosuppressive populations (Tregs, MDSCs, M2-TAMs), and antigen-presenting cells. Additionally, this review highlights the role of the gut microbiota and their metabolites (e.g., SCFAs, secondary bile acids and indoles) in remodeling the immune microenvironment via metabolic crosstalk. Overall, this work provides a comprehensive understanding of CRC metabolic reprogramming and its microenvironmental impacts, offering critical insights to guide the development of novel metabolism-targeted therapeutic strategies for CRC.